Self-Efficacy of PCK: An Exploration of Indonesian Prospective Physics Teacher Perspectives - Efwinda, Shelly; Haryanto, Zeni; Sulaeman, Nurul Fitriyah; Nuryadin, Atin (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
As physics is considered difficult to understand, prospective physics teacher programs face the challenges of providing adequate Pedagogical Content Knowledge (PCK). Future teachers' self-efficacy is an essential factor affecting their teaching performance in the classroom. This study aimed to explore the self-efficacy of prospective physics teachers in Indonesia. Data were collected through a questionnaire with a Likert scale consisting of 18 statements and reasons for scoring. The questionnaire on self-efficacy was divided into the self-efficacy domain Content Knowledge (CK), Pedagogical Knowledge (PK), and PCK. The participants were 71 final-year students from 5 Physics Education Study Programs in Indonesia. According to the results, the total self-efficacy score of prospective teachers in physics was 6.98, which falls into the high category. In the CK, PK, and PCK domains, self-efficacy was 6.91, 7.06, and 6.93, respectively, in the high category. An in-depth analysis of students who responded in the low category showed that prospective teachers with low self-efficacy tend to be unsure that they have taught well. They believe that they have not fully mastered physics material and the characteristics of diverse students. Also, they have not gained significant teaching experience. According to these results, teacher education institutions must re-evaluate what learning activities can increase prospective teachers' self-efficacy in teaching and their teaching opportunities.